Green Supply Chain Collaboration, Cost Efficiency, and Export Readiness among Indonesian Manufacturing SMEs: The Mediating Role of Process Standardization - Ahmad Faizal Rahim Ahmad Faizal Rahim; Sokha Chan Sokha Chan (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
Manufacturing SMEs in Southeast Asia face growing pressure to demonstrate environmental responsibility as buyers incorporate sustainability criteria into procurement and export supply chains. While green supply chain practices are often framed as compliance costs, collaboration with upstream and downstream partners can create efficiency benefits when environmental goals are embedded in process routines and shared standards. This study examines how green supply chain collaboration influences cost efficiency and export readiness among Malaysian manufacturing SMEs through process standardization. Drawing on relational view and operations capability logic, the model conceptualizes collaboration as joint problem solving, information sharing, and coordinated environmental practices with suppliers and customers. Survey data were collected from 412 Malaysian manufacturing SMEs across food processing, textiles, and light manufacturing. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to test direct effects and mediation. Results indicate that green collaboration is positively associated with both cost efficiency and export readiness, with process standardization operating as a partial mediator. The findings suggest that SMEs can convert environmental collaboration into economic advantage when shared routines stabilize quality, reduce waste, and improve documentation demanded by export buyers. Policy implications emphasize capability-building programs that support standard adoption, supplier engagement, and documentation tools suitable for SME constraints.